Impact of Social Media Influencers on Purchase Intention - Linta Khan; Javaria Asim (Research Journal of Psychology, 2025)
With an emphasis on the moderating function of source legitimacy, this study investigates how social media influencers affect customers' purchase intentions. Influencers on social media have grown to be important figures in influencing consumer behavior, especially among younger audience, Gen Z. This study investigates how influencer-generated content influences customers' attitudes, perceived behavioral control, and subjective norms, resulting in higher purchase intentions. It does this by drawing Source Credibility Theory. According to the study, as compared to influencers with lesser credibility, individuals with higher credibility greatly increase consumers' trust and have a beneficial effect on their buy intentions.